Encouraging meaningful reading, a challenge in the education of children for a new millennium - Mendez, Carmenza; Zuñiga, Sandra Gloria (Rastros Rostros, 2023)
The low number of children who practice reading and writing with interest, leads not only teachers, but also parents to ask themselves: Why don't children read? A question to which we can answer: because we do not do everything possible both at school and at home to train them in the culture of MEANINGFUL READING, in such a way that from the first years of schooling they find the meaning it deserves.
Keywords: meaningful reading; education; new millennium